High-breathability, light-proof, antibacterial and fresh-keeping film and preparation method thereof

By improving the interface combination of nano zinc oxide and polyethylene resin, a high breathable, light-proof and antibacterial film was prepared, which solved the problems of insufficient breathability, light-proof and antibacterial properties of fruit and vegetable fresh-proof films, and achieved efficient fresh-preservation of fruit and vegetable.

CN120248395AActive Publication Date: 2025-07-04SUZHOU ZIJIN PLASTIC

Patent Information

Application Number
CN202510677598.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-07-04
Estimated Expiration
2045-05-26

AI Technical Summary

Technical Problem

The prior art lacks a fresh-preserving film for fruits and vegetables that have high breathability, light resistance and antibacterial properties, resulting in fruits and vegetables being easily deteriorated after picking.

Method used

Alkenylated capacity-enhancing connecting agents are used to improve the interface combination between nano zinc oxide and polyethylene resin, and a high breathable, light-proof and antibacterial fresh-keeping film is prepared by blow molding and stretching processes. The alkenylated capacity-enhancing connecting agent is synthesized through epoxy-hydroxyl ring opening and ion exchange mechanisms, and the organic-inorganic hybrid composite functional components are prepared by using thiol-ene click reaction.

Benefits of technology

The prepared film has high breathability, light resistance and antibacterial properties, which significantly improves the freshness effect of fruits and vegetables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to the technical field of multifunctional films, and discloses a high-breathability light-proof antibacterial fresh-keeping film and a preparation method thereof.Based on an epoxy-hydroxyl ring-opening mechanism and an ion exchange effect, sodium citrate, allyl glycidyl ether and compatibilized long aliphatic chain quaternary ammonium salt serve as raw materials, and an alkenyl compatibilized connecting agent is prepared; based on a sulfydryl-alkene click reaction mechanism, the method comprises the following steps: modifying an alkenylation compatibilization type linking agent on the surface of silver-loaded or non-silver-loaded sulfydryl nano zinc oxide to prepare a silver-loaded or non-silver-loaded organic-inorganic hybrid composite functional component; low-density polyethylene resin and an organic-inorganic hybrid composite functional component (or a silver-loaded organic-inorganic hybrid composite functional component) are used as raw materials, and the high-breathability light-proof antibacterial fresh-keeping film is prepared through extrusion granulation, blow molding film forming and stretching processes. The film product prepared by the invention has high air permeability, light resistance and antibacterial ability, and can be used as a fresh-keeping packaging material for fruits and vegetables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fresh - keeping packaging materials for fruits and vegetables, and particularly to a highly breathable, light - shielding, antibacterial fresh - keeping film and a preparation method thereof. Background Art

[0002] Packaging is crucial for the fresh - keeping of fruits and vegetables, and plastic film is one of the most commonly used materials for packaging. After being picked, fruits and vegetables are still in a state of vital activity. The water vapor generated by their physiological functions is likely to form water droplets on the inner surface of ordinary packaging films with poor air - permeability. Microorganisms grow and reproduce by means of the water droplets generated on the inner surface of the packaging film, and biochemical reactions occur, resulting in the spoilage and deterioration of fruits and vegetables.

[0003] Antibacterial film is a kind of packaging material made by adding antibacterial agents to food packaging materials, which can effectively kill bacteria and other microorganisms on the surface of food and ensure food safety. Nano - zinc oxide has good heat resistance and strong antibacterial ability, and is often used as an antibacterial agent for the preparation of antibacterial films. It has been found that storing in the dark is beneficial to reducing the metabolic level of fruits and vegetables and maintaining good sensory and nutritional qualities. Moreover, nano - zinc oxide is also an ultraviolet - shielding agent. In addition, nano - zinc oxide can also be used as a pore - forming agent and combined with the stretching process to effectively regulate the microporous structure of the film.

[0004] With the continuous improvement of food safety, the fresh - keeping requirements for high - value fruits and vegetables are getting higher and higher. Fresh fruits and vegetables need to have the characteristics of light - shielding, air - permeability, and antibacterial properties during storage. However, there is currently no special film material for fruits and vegetables that has high air - permeability, light - shielding, and antibacterial properties on the market. Summary of the Invention

[0005] The present invention uses nano - zinc oxide with both light - shielding and antibacterial functions as a modifier for polyethylene resin. In order to effectively overcome the interfacial effect between the inorganic nano - zinc oxide and the organic polyethylene resin, an alkenylated compatibilizing linker is designed and synthesized. The interfacial bonding condition between nano - zinc oxide and the polyethylene resin matrix is improved through the self - made alkenylated compatibilizing linker, and further combined with the preparation processes of blow - molding and stretching to prepare a highly breathable, light - shielding, antibacterial fresh - keeping film.

[0006] To achieve the above - mentioned purpose, the present invention adopts the following technical solutions: A preparation method of a highly breathable, light - shielding, antibacterial fresh - keeping film, comprising the following steps: Step 1: Based on the epoxy - hydroxyl ring - opening mechanism, using sodium citrate and allyl glycidyl ether as raw materials, an intermediate of sodium allyl citrate is prepared; The intermediate of sodium allyl citrate and a compatibilizing long - chain fatty - amine quaternary salt are subjected to an ion - exchange reaction to obtain an alkenylated compatibilizing linker; Based on the thiol-ene click reaction mechanism: An alkenylated compatibilizing linker is modified onto the surface of silver-loaded or non-silver-loaded thiolated nano-zinc oxide to obtain a silver-loaded or non-silver-loaded organic-inorganic hybrid composite functional component; Step 2: Add the silver-loaded or non-silver-loaded organic-inorganic hybrid composite functional component in an amount of 1 wt% - 10 wt% based on the amount of polyethylene resin, and through extrusion granulation, blow molding, and stretching processes, a highly breathable, light-blocking, antibacterial, and fresh-keeping film is prepared.

[0007] Further, the compatibilizing long fatty chain quaternary ammonium salt is one of cetyltrimethylammonium chloride, octadecyltrimethylammonium chloride, and tetradecyltrimethylammonium chloride.

[0008] Further, the preparation method of the alkenylated compatibilizing linker is as follows: Under the catalysis of boron trifluoride diethyl ether complex, through the epoxy-hydroxy ring-opening reaction of 1 molar equivalent of sodium citrate and 1 molar equivalent of allyl glycidyl ether, an intermediate of sodium allyl citrate is prepared. Then, the intermediate of sodium allyl citrate and cetyltrimethylammonium chloride undergo an ion exchange reaction in a molar ratio of 1:3 to prepare the alkenylated compatibilizing linker.

[0009] Further, the preparation method of the silver-loaded organic-inorganic hybrid composite functional component is as follows: Silver ions coordinate with the thiol groups in the thiolated nano-zinc oxide to obtain silver-loaded thiolated nano-zinc oxide; The silver-loaded thiolated nano-zinc oxide and the alkenylated compatibilizing linker undergo a thiol-ene click reaction to obtain the silver-loaded organic-inorganic hybrid composite functional component.

[0010] Further, the blow molding process parameters are: the temperatures in zones 1 - 4 are: 90 - 110 °C, 130 - 140 °C, 150 - 170 °C, 175 - 185 °C.

[0011] Further, the stretching process is a longitudinal stretching process, and its process parameters are: the stretching temperature is 80 - 100 °C, and the stretching ratio is 1 - 5 times.

[0012] Further, the particle size of the nano-zinc oxide used in the thiolated nano-zinc oxide is 20 - 50 nm.

[0013] Further, the thickness of the highly breathable, light-blocking, antibacterial, and fresh-keeping film is 10 - 20 μm.

[0014] Further, the highly breathable, light-blocking, antibacterial, and fresh-keeping film can be used as a fresh-keeping packaging material for fruits and vegetables.

[0015] The beneficial effects of the present invention are as follows: Based on the epoxy ring-opening and ion-exchange mechanisms, using sodium citrate, allyl glycidyl ether, and cetyltrimethylammonium chloride as raw materials, an alkenylated compatibilizing linker was synthesized; Based on the thiol-ene click chemistry mechanism, the alkenylated compatibilizing linker was grafted onto the surface of thiolated nano-zinc oxide (or silver-loaded thiolated nano-zinc oxide) to obtain an organic-inorganic hybrid composite functional component (or silver-loaded organic-inorganic hybrid composite functional component); Using low-density polyethylene resin and the organic-inorganic hybrid composite functional component (or silver-loaded organic-inorganic hybrid composite functional component) as raw materials, through blow molding and stretching processes, a highly breathable, light-blocking, antibacterial, and fresh-keeping film product was prepared; The experimental results proved that: the film product prepared by the present invention has excellent properties of high breathability, light-blocking, and antibacterial. Detailed implementation mode Experimental example 1:

[0016] To prepare an organic-inorganic hybrid composite functional component, the following steps are included: (1) Preparation of allyl sodium citrate intermediate, and its preparation mechanism is: under the catalysis of boron trifluoride diethyl ether complex, through the ring-opening reaction of the hydroxyl group in sodium citrate with the epoxy group in allyl glycidyl ether, the allyl sodium citrate intermediate was prepared. The specific experimental steps are as follows: under nitrogen protection, 3 g of sodium citrate and 0.05 g of boron trifluoride diethyl ether complex were added to 50 mL of an ethanol aqueous solution with a volume fraction of 70%, stirred evenly, then 1.4 g of allyl glycidyl ether was added and mixed evenly. The temperature of the system was raised to 50 °C and stirred for 6 h. Then, the pH value of the system was adjusted to 7 with ammonia water, the solvent was removed by rotary evaporation, filtered, the product was collected, and vacuum dried at 60 °C for 5 h to obtain the allyl sodium citrate intermediate; The chemical structural formula of the allyl sodium citrate intermediate is: ; (2) Preparation of alkenylated compatibilizing linker, and its preparation mechanism is: based on the ion-exchange mechanism, cetyltrimethylammonium chloride and the allyl sodium citrate intermediate undergo an ion-exchange reaction to prepare the alkenylated compatibilizing linker. The specific experimental steps are as follows: 2.6 g of cetyltrimethylammonium chloride was dissolved in 100 mL of deionized water at 60 °C to obtain a hot solution a; 1 g of the allyl sodium citrate intermediate was dissolved in 50 mL of deionized water at 60 °C to obtain a hot solution b; then the two hot solutions were mixed, sodium chloride was precipitated, cooled to room temperature under stirring conditions, separated and filtered, washed with deionized water, and vacuum dried at 50 °C for 6 h to prepare the alkenylated compatibilizing linker; The chemical structural formula of the alkenylated compatibilizing linker is: ; The 1H NMR characterization of the alkenylation compatibilizing linker is as follows: 1 H NMR(DMSO-d6, 400MHz)δ: 0.88 - 0.90 (t, 9H), 1.27 - 1.35 (m, 78H), 1.37 - 1.48 (m, 6H), 1.62 (s, 18H), 1.66 (s, 9H), 1.84 - 2.00 (m, 6H), 2.75 - 2.87 (m, 4H), 3.44 - 3.57 (m, 4H), 3.90 - 3.96 (m, 1H), 4.01 - 4.02 (d, 2H), 4.38 - 4.39 (d, 1H), 5.15 - 5.27 (dd, 2H), 5.83 - 5.93 (m, 1H); (3) Preparation of mercapto-functionalized nano-zinc oxide, and the specific experimental steps are as follows: Place 2 g of nano-zinc oxide (particle size of 30 nm) in 50 mL of anhydrous ethanol, ultrasonically disperse for 20 min, add 1.3 g of 3-mercaptopropyltriethoxysilane, mix well, raise the temperature to 60 °C, stir and react for 6 h, then filter and separate the obtained mixture, wash it, and dry it in a vacuum drying oven at 60 °C for 8 h to obtain mercapto-functionalized nano-zinc oxide; The chemical structural formula of mercapto-functionalized zinc oxide is: ; (4) Preparation of an organic-inorganic hybrid composite functional component, and its preparation mechanism is as follows: Under the action of a benzoin dimethyl ether initiator, through the thiol-ene click chemical reaction between the alkenyl functional groups in the alkenylation compatibilizing linker and the thiol groups in the mercapto-functionalized nano-zinc oxide, an organic-inorganic hybrid composite functional component is prepared. The specific experimental steps are as follows: Add 2 g of mercapto-functionalized nano-zinc oxide and 3.8 g of alkenylation compatibilizing linker to 100 mL of acetone, stir and mix evenly, add 0.1 g of benzoin dimethyl ether initiator, stir and react for 3 h under the irradiation of an ultraviolet lamp (365 nm, 25 w), rotary evaporate to remove acetone, filter, collect the product, and dry it in a vacuum at 60 °C for 3 h to prepare an organic-inorganic hybrid composite functional component. Experimental Example 2:

[0017] Due to the relatively wide bandgap of the photocatalyst of nano-zinc oxide, it can only be excited in the ultraviolet region with a relatively short wavelength (about 375 nm). Therefore, under conditions that do not meet the excitation wavelength or insufficient light conditions, the antibacterial effect of nano-zinc oxide will be restricted or unable to play, and the purpose of anti-biofouling cannot be achieved. Silver ions have a strong inhibitory and killing effect on microorganisms. Therefore, the present invention conceives a silver-loaded mercapto-functionalized nano-zinc oxide antibacterial agent. When there is no light or ultraviolet light, silver ions can still play an antibacterial role alone. When there is light or ultraviolet light, nano-zinc oxide and silver ions can play an antibacterial role synergistically, effectively supplementing the deficiency of nano-zinc oxide antibacterial and solving the problem of the high price of silver ions; Replace the mercapto-functionalized nano-zinc oxide in Experimental Example 1 with silver-loaded mercapto-functionalized nano-zinc oxide to prepare a silver-loaded organic-inorganic hybrid composite functional component. The preparation method of silver-loaded mercapto-functionalized nano-zinc oxide is as follows: Through the strong coordination effect between some mercapto groups in mercapto-functionalized nano-zinc oxide and silver ions, silver is loaded on the surface of nano-zinc oxide to obtain silver-loaded mercapto-functionalized nano-zinc oxide. The specific experimental steps are as follows: Place 2.5 g of mercapto-functionalized nano-zinc oxide in 50 mL of deionized water, stir evenly, then add 2 mL of AgNO3 solution with a concentration of 1 mol / L, stir and react for 2 h, then centrifuge and separate, wash, and collect the washing solution for detecting the silver ion loading amount. Vacuum dry at 60 °C for 4 h to obtain silver-loaded mercapto-functionalized nano-zinc oxide; According to the color reaction of 1,10-phenanthroline-bromopyrogallol red forming a ternary complex with silver ions, the mass concentration of silver ions in the washing solution of silver-loaded mercapto-functionalized nano-zinc oxide is determined by spectrophotometry. The silver ion loading amount is calculated according to the following formula: Q = (1.50 - cV) × 63.5% / m0, where Q is the amount of silver ions loaded per gram of silver-loaded mercapto-functionalized nano-zinc oxide, g / g; c is the mass concentration of silver nitrate in the washing solution, g / mL; V is the volume of the silver nitrate solution, mL; m0 is the mass of mercapto-functionalized nano-zinc oxide, g. After testing, the silver ion loading amount is 86 mg / g. Example 1:

[0018] A highly breathable, light-blocking, antibacterial and fresh-keeping film a, comprising the following raw materials in parts by weight: 100 parts of low-density polyethylene resin (grade DFDJ4960); 6 parts of organic-inorganic hybrid composite functional component; The preparation method of the highly breathable, light-blocking, antibacterial and fresh-keeping film comprises the following steps: Step 1: According to the formula of the highly breathable, light-blocking, antibacterial and fresh-keeping film a, ingredients are prepared. Low-density polyethylene resin and an organic-inorganic hybrid composite functional component are added to a mixer. After stirring and mixing, the mixed material is poured into a twin-screw extruder for extrusion granulation. Among them, the screw speed is 30 r / min, and the temperatures of zones 1-4 are: 125 °C, 165 °C, 175 °C, 175 °C. Then the pellets are placed in a vacuum drying oven and dried at 80 °C for 4 h to obtain mixed masterbatch; Step 2: The obtained mixed masterbatch is blown into a film using a single-screw extruder by the upward blowing method. Among them, the screw speed during film blowing is 35 r / min, and the temperatures of zones 1-4 are: 100 °C, 135 °C, 160 °C, 180 °C, to produce a film with a thickness of 80 μm; Step 3: The film with a thickness of 80 μm is longitudinally stretched. The stretching temperature is set at 90 °C, the stretching ratio is 5 times, the initial speed is 0.5 m / min, and after stretching, it is kept for shape heat treatment at 200 °C for 5 s to prepare the highly breathable, light-blocking, antibacterial and fresh-keeping film a. Example 2:

[0019] Prepare the highly breathable, light-blocking, antibacterial and fresh-keeping film b, and the difference between it and the highly breathable, light-blocking, antibacterial and fresh-keeping film a is only that: the dosage of the organic-inorganic hybrid composite functional component is 1 part by weight. Example 3:

[0020] Prepare the highly breathable, light-blocking, antibacterial and fresh-keeping film c, and the difference between it and the highly breathable, light-blocking, antibacterial and fresh-keeping film a is only that: the dosage of the organic-inorganic hybrid composite functional component is 10 parts by weight. Example 4:

[0021] Prepare the highly breathable, light-blocking, antibacterial and fresh-keeping film d, and the difference between it and the highly breathable, light-blocking, antibacterial and fresh-keeping film a is only that: the organic-inorganic hybrid composite functional component is replaced with a silver-loaded organic-inorganic hybrid composite functional component. Comparative example:

[0022] Prepare a polyethylene film, and the difference between it and the highly breathable, light-blocking, antibacterial and fresh-keeping film a is only that: the organic-inorganic hybrid composite functional component is not used. Performance test:

[0023] I. Antibacterial performance test: Escherichia coli and Staphylococcus aureus were used as test strains. Escherichia coli and Staphylococcus aureus were cultured at 37°C for 24 h and diluted to 10^6 colony forming units (CFU) per milliliter. 0.1 g of the sample was added to 10 mL of the bacterial dilution, and irradiated at room temperature for 2 h under 120 W white light conditions. Then, 0.1 mL of the solution was dropped onto an AGAR plate and evenly spread, and placed at 37°C for 12 h. Then, the relative antibacterial rate was calculated and averaged. The calculation formula is: relative antibacterial rate = (P - M) / P × 100%, where P and M are the average numbers of bacteria in the control group and the experimental group samples, respectively; Among them, the model of Escherichia coli is ATCC 25922; the model of Staphylococcus aureus is ATCC 6538; The above test results are shown in Table 1 below; Table 1 Antibacterial performance test results of the highly breathable light-shielding antibacterial fresh-keeping film

[0024] II. Light-shielding performance test: The ultraviolet light transmittance of the sample was tested according to GB / T 2410-2008 Determination of Transmittance and Haze of Transparent Plastics. The test wavelength range was 250 - 800 nm, and the transmittance of the sample at 380 nm was recorded; III. Breathability performance test: The oxygen transmission rate (OTR) of the sample was calculated according to GB / T 1038.1-2022 Plastics - Films and Sheets - Methods of Test for Gas Transmission - Part 1: Differential Pressure Method; the water vapor transmission rate (WVP) of the sample was calculated according to GB / T 1037-2021 Determination of Water Vapor Transmission of Plastic Films and Sheets - Cup Method for Weight Gain and Loss. The test conditions were a temperature of 23°C and a relative humidity of 50%. Each group of samples was measured 3 times and averaged; IV. Mechanical property test: The mechanical property test was carried out according to GB / T 1040.3-2006. The specific test steps were as follows: A 20 mm × 150 mm sample was fixed on a tensile testing machine, and tensile testing was carried out at a tensile rate of 50 mm / min, and the tensile strength of the sample was recorded; The above test results are shown in Table 2 below; Table 2 Performance test results of the highly breathable light-shielding antibacterial fresh-keeping film

[0025] From the experimental data in Table 1 and Table 2, the following conclusions can be drawn: Compared with the prior art, the highly breathable light-shielding antibacterial fresh-keeping film prepared by the present invention has achieved beneficial technical effects of significant improvement in breathability performance, light-shielding performance, antibacterial ability and mechanical properties.

Claims

1. A preparation method of a highly breathable, light-blocking, antibacterial and fresh-keeping film, characterized in that, It includes the following steps: Step 1: Based on the epoxy-hydroxy ring-opening mechanism, using sodium citrate and allyl glycidyl ether as raw materials, prepare the sodium allyl citrate intermediate; The sodium allyl citrate intermediate and the compatibilizing long fatty chain quaternary ammonium salt undergo ion exchange to prepare the alkenylated compatibilizing linker; Based on the thiol-ene click reaction mechanism: Modify the alkenylated compatibilizing linker onto the surface of silver-loaded or non-silver-loaded thiolated nano-zinc oxide to prepare the silver-loaded or non-silver-loaded organic-inorganic hybrid composite functional component; Step 2: Add the silver-loaded or non-silver-loaded organic-inorganic hybrid composite functional component according to 1 wt% - 10 wt% of the polyethylene resin dosage, and through extrusion granulation, blow molding and stretching processes, prepare the high gas permeability, light-blocking, antibacterial and fresh-keeping film.

2. The preparation method of a highly breathable, light-blocking, antibacterial and fresh-keeping film according to claim 1, characterized in that The compatibilizing long fatty chain quaternary ammonium salt is one of cetyltrimethylammonium chloride, octadecyltrimethylammonium chloride, and tetradecyltrimethylammonium chloride.

3. The preparation method of a highly breathable, light-blocking, antibacterial and fresh-keeping film according to claim 2, characterized in that, The chemical structural formula of the alkenylated compatibilizing linker is: 。 4. The preparation method of a highly breathable, light-blocking, antibacterial and fresh-keeping film according to claim 3, characterized in that, The preparation method of the alkenylated compatibilizing linker is: Under the catalytic action of boron trifluoride diethyl ether complex, through the epoxy-hydroxy ring-opening reaction of 1 molar equivalent of sodium citrate and 1 molar equivalent of allyl glycidyl ether, prepare the sodium allyl citrate intermediate, and then the sodium allyl citrate intermediate and cetyltrimethylammonium chloride undergo ion exchange according to a molar ratio of 1:3 to prepare the alkenylated compatibilizing linker.

5. The preparation method of a highly breathable, light-blocking, antibacterial and fresh-keeping film according to claim 1, characterized in that, The preparation method of the silver-loaded organic-inorganic hybrid composite functional component is: Silver ions and the thiol groups in the thiolated nano-zinc oxide undergo coordination to prepare silver-loaded thiolated nano-zinc oxide; The silver-loaded thiolated nano-zinc oxide and the alkenylated compatibilizing linker undergo a thiol-ene click reaction to prepare the silver-loaded organic-inorganic hybrid composite functional component.

6. The preparation method of a highly breathable, light-blocking, antibacterial and fresh-keeping film according to claim 1, characterized in that, The blow molding process parameters are: the temperatures in zones 1 - 4 are: 90 - 110 °C, 130 - 140 °C, 150 - 170 °C, 175 - 185 °C.

7. The preparation method of a highly breathable, light-blocking, antibacterial and fresh-keeping film according to claim 1, characterized in that, The stretching process is a longitudinal stretching process, and its process parameters are: the stretching temperature is 80 - 100 °C, and the stretching ratio is 1 - 5 times.

8. The preparation method of a highly breathable, light-blocking, antibacterial and fresh-keeping film according to claim 1, characterized in that, The particle size of the nano-zinc oxide used in the thiolated nano-zinc oxide is 20 - 50 nm.

9. A highly breathable, light-blocking, antibacterial and fresh-keeping film prepared by the method according to any one of claims 1 to 8, characterized in that, The thickness of the high gas permeability, light-blocking, antibacterial and fresh-keeping film is 10 - 20 μm.

10. The application of a highly breathable, light-blocking, antibacterial and fresh-keeping film according to claim 9, characterized in that, The high gas permeability, light-blocking, antibacterial and fresh-keeping film can be used as a fresh-keeping packaging material for fruits and vegetables.

Citation Information

Patent Citations

  • Polydimethyldiallylammonium chloride modified color fixing agent and preparation method thereof

    CN103015239A

  • Antibacterial and antistatic tear-resistant thin-film material

    CN105315553A

  • Method for preparing SiO2 silver-loaded mould-proof fresh-keeping packaging bag

    CN106543540A

  • Antibacterial polyethylene food packaging film and preparation method thereof

    CN109054145A

  • Bagging composite material for fruits and vegetables, preparation method therefor and application of bagging composite material

    CN111820057A

Cited By

  • Antibacterial film material and preparation process thereof

    CN121673675A